Lived Experience of Public School Teachers as Poll Workers during the 2022 National and Local Elections - Rebucas, Honey Lou B.; Albellar, Diana Rose T.; Ranises, Lloyd B.; Caballeda, Arah H.; Baluyos, Genelyn R. (PT ARRUS Intelektual Indonesia, 2025)
Teachers have many different roles in society that are significant and valuable. Aside from performing the noble task of teaching the country's young citizens, teachers are also called to man the polling precincts every election day. Their duties are to ensure free, honest, and clean elections. Specifically, they should prevent any attempt to manipulate the results to benefit any candidate or party. This study will describe and understand the lived experience of public-school teachers who served as poll workers during the 2022 national and local elections. A phenomenological approach was utilized as a research design. Ten public school teachers who served as poll workers during the 2022 federal and provincial elections were considered study participants. They were selected through purposive sampling. An interview guide was used to gather the data. The Hyper-Research software identified the codes derived from the interview results to formulate the themes. Analysis of the responses was done using Moustaka's transcendental phenomenology. Results generated six themes, namely: (1) Being prepared to apply in the Training; (2) Experiencing Technical Difficulties; (3) Experiencing Internet Instability; (4) Experiencing Psychological Differences; (5) Using Coping Strategies; and (6) Being Fulfilled and Satisfied in the Job. The participants had a variety of experiences while serving on the electoral board. This includes their readiness to apply their training learning, encountering technical difficulties, experiencing internet instability, and, as a result, encountering psychological differences. Despite their difficulties, they dealt with them effectively by employing coping strategies. They have been through various good and bad situations, but they have shown such dedication to their work that they still feel satisfied and fulfilled despite the sleepless nights and starvation. This study recommended that all electoral board members should have adequate training to ensure that everyone knows what to do in case unpredictable circumstances happen so that they can respond immediately.